The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/capr.12156
|View full text |Cite
|
Sign up to set email alerts
|

When life gets in the way: Systematic review of life events, socioeconomic deprivation, and their impact on counselling and psychotherapy with children and adolescents

Abstract: Background Life events are recognised to link low socio‐economic status (SES) with impaired mental health. Despite attention to patients’ historical environmental circumstances in psychotherapeutic practice, events that occur over the course of counselling and psychotherapy (‘intercurrent’ events) seem to have received little attention in research. Method Life events were defined to include those that are chronic and severe, as well as minor, everyday occurrences. Outcomes were restricted to internalising prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…‘Troubled’ dropouts most certainly would have met the criteria for a number of risk factors, and therefore according to Kazdin’s risk-factor model, would have been considered at high risk of dropout. A recent systematic review revealed that intercurrent life events and contextual factors that interfere with treatment have been largely overlooked in the child psychotherapy literature (Blackshaw et al, 2018). ‘Troubled’ dropouts represent a group of young people for whom there were contextual factors that impeded their ability to engage in treatment, reflecting the need for greater attention to be paid to such contextual complexity for delivering effective mental health care.…”
Section: Discussionmentioning
confidence: 99%
“…‘Troubled’ dropouts most certainly would have met the criteria for a number of risk factors, and therefore according to Kazdin’s risk-factor model, would have been considered at high risk of dropout. A recent systematic review revealed that intercurrent life events and contextual factors that interfere with treatment have been largely overlooked in the child psychotherapy literature (Blackshaw et al, 2018). ‘Troubled’ dropouts represent a group of young people for whom there were contextual factors that impeded their ability to engage in treatment, reflecting the need for greater attention to be paid to such contextual complexity for delivering effective mental health care.…”
Section: Discussionmentioning
confidence: 99%
“…Also, socio-economic adversities, including poverty and environmental risk factors, have been associated with the onset and maintenance of psychopathological symptoms and low life satisfaction ( 27 ). This relationship has been explained through material deprivation but also increased adverse life events (such as unemployment, abuse and neglect), with consequences for treatment outcomes, including among children and adolescents [e.g., ( 28 )]. Given the recent recession period and current socio-economic strain for many individuals, it seems relevant to recognize that people living in poverty are more likely to experience mental health problems ( 29 ), less likely to access treatment ( 30 ) and less likely to achieve full recovery from emotional psychopathological problems ( 31 ).…”
Section: Explaining Psychopathology: the Role Of Culture Discriminatmentioning
confidence: 99%
“…Unfortunately, minimal research attention has been devoted to the influence of SLEs on treatment effectiveness with EA clients; however, research with adolescent and adult samples has found that SLEs limit effectiveness (Blackshaw et al, 2018). Kraus et al (2016), for example, noted that SLEs typically predict symptom and life‐functioning treatment outcomes, and variations in counselor effectiveness are in part attributable to the influence of SLEs on client outcomes.…”
Section: Stressful Life Events and Flourishingmentioning
confidence: 99%